Inventory Invasive Plant in ITB Campus Ganesha - Wiguna - Nim: 10611048, Agung
Invasive plants are plants that can successfully occupy and spread in new habitats. Currently in Indonesia invasive plants are reported to have invaded various places, around settlements to national parks. Invasive species can be the result of intentional introductions made in the form of ornamental plants to fill the gardens. The introduction of the alien species has the potential to interfere with the environment in which the plant is located. The foreign species themselves are species that live outside their natural habitat. ITB Campus Ganesha with an area of about 286,830 m2 has diverse vegetation. Most of the vegetation is in the form of green open spaces or small parks. The purpose of the study was to evaluate the possibility of invasive plant presence in the ITB Campus Ganesha. The study was conducted as a first step in controlling the population of invasive species in the ITB Campus Ganesha. The data was collected by using the roaming method as far as 3.6 km along the road corridor that existed in ITB Campus Ganesha. The 3.6 kilometer observation line is divided into 36 plots with a length of 100 m/plot. Observations included recording the names of identified plant species in each plot and their frequencies. The observation result shows that there are 165 species in the ITB Campus Ganesha belonging to 60 families. Of the 165 species, 125 species are foreign species or 76% of the total plant. This amount is much higher when, compared to local species which is only 24%. The species with the highest frequency found in the ITB Campus Ganesha is Kylinga nemoralis with a frequency value of 0.86, but not classified as invasive plants based on ISSG. Invasive alien invasive plants found in 18 species. Invasive alien species are Oxalis corniculata, Ageratum conyzoides, Sansevieria trifasciata, Furcraea foetida, Impatiens walleriana, Mikania micrantha, Psidium guajava, Elephantopus mollis, Lantana camara, Cyperus rotundus, Elaeis guineensis, Leucaena leucocephala, Agave americana, Bambusa vulgaris, Mimosa pudica, Imperata cylindrica, Paspalum scrobiculatum and Passiflora edulis. From the results obtained can be concluded that ITB Campus Ganesha has foreign plants higher than local plants but not all foreign plants are invasive plants.